Persepsi Masyarakat dan Pemerintah Desa terhadap Kebijakan Pengembangan Bum Desa Sektor Pariwisata: Studi Kasus Desa Gunungrejo, Kabupaten Malang - Muhammad Irfan Islami (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Provinsi Sumatera Utara, 2025)
Gunungrejo Village is predominantly inhabited by residents who work as farmers and, on the other hand, it has a potential natural tourism object. This research aims to analyze the perception of the village government and its communities regarding development policy of the Village-Owned Enterprise (BUM Desa) in the tourism sector. This study is qualitative research with a case study approach. Data collection methods included observation, interviews, and documentation. Informants were selected based on purposive sampling method. The research shows that the government has chosen the tourism sector as the new engine of growth. The village residents generally comply with this decision. However, those who are part of the farming community hope that the Village-Owned Enterprise (BUM Desa) can contribute more to the agricultural sector. Keywords: Village-Owned Enterprise (BUM Desa); Village government; Vilage communities; tourism, agriculture